Review of Implementing the Internet of Things (IoT) for Robotic Drones (IoT Drones) - Hajjaj S.S.H.; Moktar M.H.; Weng L.Y. (EDP Sciences, 2025)
Drone and the Internet of Things are different technologies, actively utilised and implemented across various fields. Connectivity is the difference between the IoT drone and the regular drone. IoT drones can receive and transmit data and command signals in real-time while being controlled through the IoTnetwork. By implementing both drone and IoT, the flying IoT (IoT-Drone) is built as a new form of IoTdevice. This work improves how to use the drone effectively in many aspects; data transferring, data collecting, real-time monitoring, and control. With the emergence of the Internet of Things, Artificial Intelligence, and advanced communication, the IoT drone technology has been utilized in many fields, especially in agriculture and inspection, and discussed in smart cities, logistic delivery, and the military. This paper reviews the IoT drone implementation in those fields and reviews the researchers' discussionand studies on IoT drone optimization. ? The Authors, published by EDP Sciences. This is an open access article distributed under the terms of the Creative Commons Attribution License 4.0 (https://creativecommons.org/licenses/by/4.0/).